The cure performance of modified ZrO2 coated by paraffin via projection based stereolithography. Issue 3 (15th February 2019) - Yanhui, Li; Yong, Chen; Minglang, Wang; Lian, Li; Haidong, Wu; Fupo, He; Shanghua, Wu
Abstract: Projection based stereolithography (pSL) is widely applied to fabricate complicated ceramic parts. The preparation of ceramic suspension is critical for the process, especially, since large refractive index difference between ceramic and photosensitive resin would lead to an intense light scattering. In this paper, a ball-milling method is used to coat ZrO2 with paraffin that has a similar refractive index to that of resin, and the coated layer is measured to be around 10 nm. The modified ZrO2 is characterized by IR and TEM, and the photocuring behaviors are also investigated in terms of cure depth and excess cure width. The cure depth of modified ZrO2 increases by13.2% and 16.8% compared to the one without coating. At the same time, the excess cure width decreases by 77.1% and 62.7% using the same projection time. Moreover, ceramic ring prepared with the modified ZrO2 has a shrinkage of about 27.2%, and a density of 91.8%, smaller than the one prepared with ZrO2 without coating due to a burnout of paraffin. In conclusion, the paraffin coating layer could reduce the light scattering and thus improve the curing performance of ZrO2 suspension，especially, the excess cure width.